Geo ateliê: atualização formativa para professores ao ensinar geografia para alunos surdos - Ribeiro, Ivana dos Santos; Batalliotti, Elene Soellyn (Universidade Estadual Paulista (UNESP), 2024)
The research entitled "The teaching of geography through Libras for students deaf in the city of Mata de São João -Bahia", aimed to analyze how the inclusion of deaf students occurs from the pedagogical practice of Geography teachers from the regular school system in the city of Mata de São João - Bahia, and as an Educational resource to propose a formative update plan that meets the inclusive education of these students. The Educational resource called Geo ateliê: formative update for teachers when teaching geography to deaf students is a course with the character of formative updating for geography teachers in the final years of Elementary School, who work with Deaf and hearing students in the classroom. The purpose of this course is to guide geography teachers to the development of knowledge and educational practices necessary for the production of methodological proposals for the teaching of geography, which stimulate the autonomy, the critical sense of the deaf and hearing student for the understanding and application of geographical reasoning in the process of production of space.
O recurso Educacional GEO ATELIÊ : atualização formativa para professores ao ensinar geografia para alunos surdos é um desdobramento da dissertação intitulada : O ensino da geografia por meio da Libras para alunos surdos da cidade de Mata de São João – Bahia desenvolvida no Programa de Mestrado Profissional em Educação Inclusiva em Rede Nacional – PROFEI, da Universidade Estadual Paulista, Júlio de Mesquita Filho - UNESP, campus Presidente Prudente.
Keywords: Surdos - educação; Geografia; Professores; Estudo e ensino; Formação